Perceived sustainability of the school-based social and behavior change communication (SBCC) approach on malaria prevention in rural Ethiopia: stakeholders' perspectives - Fira Abamecha; Gachena Midaksa; Morankar Sudhakar; Lakew Abebe; Yohannes Kebede; Guda Alemayehu; Zewdie Birhanu (BMC, 2021)
Abstract Background Evidence on what makes the school-engaged social and behavior change communication (SBCC) interventions on malaria prevention more sustainable are limited in literature partly due to its recent emergence. Enrolling the key stakeholders, this study explored the perceived sustainability of the SBCC interventions on malaria prevention through primary school communities in rural Ethiopia. Methods The SBCC interventions were implemented from 2017 to 2019 in 75 primary schools and villages in rural Jimma to promote malaria preventive practices. As a part of program evaluation, this study employed a mixed-method to collect qualitative and quantitative data from 205 stakeholders following the end of the program. Data were collected using interview guides and structured questionnaires. The SPSS version 26 and Atlas ti7.1 software were used to analyze the data. Multivariable linear regression modeling was used to identify predictors of the perceived sustainability of the program (SOP). Results The mean score of SOP was 25.93 (SD = 4.32; range 6-30). Multivariable linear regression modeling showed that the perceived risk to malaria (β = 0.150; P = 0.029), self-efficacy (β = 0.192; P = 0.003), and perceived fidelity of implementation (β = 0.292; P = 0.000) and degree of adoption (β = 0.286; P = 0.000) were positively predicted the perceived SOP. The qualitative result identified various barriers and opportunities to sustaining the program that summarized under three themes which include perceptions about the quality of program delivery (e.g inadequate involvement of stakeholders and staffs, concerns over short project life, immature sustainability efforts), school settings (e.g schools' malaria priority, schools' climate and quality of coaching) and the outer settings (e.g existing structures in the health and education systems). Conclusion The study identified key predictive variables such as stakeholders' perceived risk to malaria, self-efficacy, perceived fidelity of implementation and degree of adoption that could help to improve the sustainment of the school-based SBCC approach on malaria prevention and control. Further longitudinal study should be conducted to examine the rate of decline in program components over time and how improved sustainability would contribute to the effectiveness on malaria preventive behaviors among students.